Targeted and modular architectural polymers employing bioorthogonal chemistry for quantitative therapeutic delivery. Issue 12 (6th March 2020) - Ediriweera, Gayathri R.; Simpson, Joshua D.; Fuchs, Adrian V.; Venkatachalam, Taracad K.; Van De Walle, Matthias; Howard, Christopher B.; Mahler, Stephen M.; Blinco, James P.; Fletcher, Nicholas L.; Houston, Zachary H.; Bell, Craig A.; Thurecht, Kristofer J.
Abstract : There remain several key challenges to existing therapeutic systems for cancer therapy, such as quantitatively determining the true, tissue-specific drug release profile in vivo, as well as reducing side-effects for an increased standard of care. Abstract : There remain several key challenges to existing therapeutic systems for cancer therapy, such as quantitatively determining the true, tissue-specific drug release profile in vivo, as well as reducing side-effects for an increased standard of care. Hence, it is crucial to engineer new materials that allow for a better understanding of the in vivo pharmacokinetic/pharmacodynamic behaviours of therapeutics. We have expanded on recent "click-to-release" bioorthogonal pro-drug activation of antibody-drug conjugates (ADCs) to develop a modular and controlled theranostic system for quantitatively assessing site-specific drug activation and deposition from a nanocarrier molecule, by employing defined chemistries. The exploitation of quantitative imaging using positron emission tomography (PET) together with pre-targeted bioorthogonal chemistries in our system provided an effective means to assess in real-time the exact amount of active drug administered at precise sites in the animal; our methodology introduces flexibility in both the targeting and therapeutic components that is specific to nanomedicines and offers unique advantages over other technologies. In this approach, the in vivo click reaction facilitates pro-drug activation as well as provides a quantitative means to investigate the dynamic behaviour of the therapeutic agent.